2019
DOI: 10.1002/gps.5121
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenic obesity predicts nonremission of late‐life depression

Abstract: Background/objectives Aging‐related physiological changes like metabolic dysregulation and physical frailty are associated with depression and worsen its prognosis. Since central obesity is a key component of the metabolic syndrome and sarcopenia of physical frailty, we examined the association of sarcopenic obesity with depression cross‐sectional and over time. Methods Cohort study of depressed patients and a nondepressed comparison group. Setting Primary and secondary mental health care. Participants Three h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 61 publications
0
20
1
Order By: Relevance
“…A previous study found that abdominal obesity (waist circumference) exerts a modification effect on both handgrip strength and depression, reminding us that obesity combined with low handgrip strength exerts a cumulative effect on the risk of depression. 34 In addition, other studies have reported that depression combined with obesity among older adults can lead to lower handgrip strength. 35 Our study did not find any differences in any BMI stratum.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that abdominal obesity (waist circumference) exerts a modification effect on both handgrip strength and depression, reminding us that obesity combined with low handgrip strength exerts a cumulative effect on the risk of depression. 34 In addition, other studies have reported that depression combined with obesity among older adults can lead to lower handgrip strength. 35 Our study did not find any differences in any BMI stratum.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the presence of sarcopenia and low muscle strength was proposed as one possible mechanism explaining the increased fall risk associated with frailty (Hayashi et al, 2019;Kokkeler, Berg, Comijs, Oude Voshaar, & Marijnissen, 2019;Szlejf, Suemoto, & Brunoni, 2018). The interaction between SSRI usage and frailty might be explained by the biological effects of the antidepressants on the central nervous system, such as sedation (Ray, 1992), the cardiovascular system, causing postural hypotension (Halper & Mann, 1988) and anticholinergic activity (Fick, Semla, Beizer, & American Geriatrics Society, 2015), affecting the capability to maintain the integrity of one's gait and motor function and increasing the risk of falls.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanisms connecting depression to accelerated ageing are not well understood, depression has been associated with ageing at the molecular level, for example, DNA damage and mitochondrial dysfunction, the cellular level, for example, telomere attrition, protein accumulation and abnormal secretory patterns, and lastly, at the tissue and system level, for example, sarcopenia and metabolic diseases. [32][33][34][35][36] Our study also connects depression to a clinical level of senescence, namely frailty. From a clinical perspective, depressed older patients should be considered at increased risk of becoming frail and thus constitute a sample suitable for selective prevention of frailty.…”
Section: Reciprocal Associations Between Depression and Frailtymentioning
confidence: 95%